Implementasi Gerakan Literasi Sabtu Budaya Dalam Membentuk Karakter Sosial Peserta Didik di SD Negeri 1 Waringin - Nurhimayati, Husna; Muzakkar, Abdullah; Parhanuddin, L. (Jurnal Ilmiah Global Education, 2025)
This study aims to describe the implementation process of the Cultural Saturday Literacy Movement (Gerakan Literasi Sabtu Budaya / GLSB) in shaping students’ social character at SD Negeri 1 Waringin. A qualitative approach with a case study method was employed. Data were collected through in-depth interviews, participatory observations, and documentation involving the principal, teachers, students, and parents. Data were analyzed using the interactive model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing. The findings reveal that the implementation of GLSB is systematically carried out through three main stages: planning, implementation, and evaluation. Literacy activities integrated with local arts and culture foster students’ active participation and strengthen social character values such as cooperation, discipline, responsibility, tolerance, empathy, and care for others. The success of the program is supported by strong collaboration among the school, teachers, parents, and the community. Meanwhile, its challenges include limited facilities, time constraints, and varying levels of teacher competence in integrating cultural values into the learning process.